A new random perturbation interval of symmetric eigenvalue problem. Issue 1 (2nd January 2021) - Tang, Ling; Xiao, Chuanfu; Li, Hanyu
Abstract : A large interval of random perturbation is presented in this study. Under the derived interval, the probability that the simple eigenvalue of original symmetric matrix is still simple is not less than a given confidence level. Numerical examples are provided to illustrate the obtained results.